An Executive Review of Sludge Pretreatment Techniques - Tuan, Le Ngoc; Châu, Phạm Ngọc (Vietnam Journal of Science and Technology, 2014)
Anaerobic digestion of sludge has been an efficient and sustainable technology for sludge treatment but the low microbial conversion rate of its first stage requires sludge pretreatment, such as biological (aerobic, anaerobic conditions), thermal, mechanical (ultrasonication, lysis-centrifuge, liquid shear, grinding), and chemical (oxidation, alkali, acidic pretreatment, etc.) techniques. This work aims at presenting a review and a short comparison of these common sludge pretreatment techniques, serving the selection of the most suitable technique for lab scale research and for subsequent actual application.